Ghana's Microfinance Sector : Challenges, Risks and Recommendations - World Bank Group (World Bank, Washington, DC, 2018)
Broadening and deepening financial inclusion in Ghana is important for ensuring inclusive growth and achieving the objectives of the Financial Sector Strategic Plan. Deeper and more inclusive financial sectors allow poor households to manage risks and smooth consumption; they provide opportunities for very micro and small enterprises to survive and grow; they can bridge geographical dispersion by providing access to savings and payment services to populations in rural and remote regions. Ghana fares well on some indicators of financial inclusion compared to other Sub-Saharan African countries, and is comparable to lower middle-income countries. However, it lacks a clear strategy for financial inclusion and development of microfinance institutions (MFIs) and other methodologies of making financial services more widely available. Microfinance - the provision of savings, credit, and other financial products to the poor - grew rapidly in Ghana during the 2000s in existing institutions, performing well by international benchmarks for MFIs and raising the percentage of the population that is financially included.5 While the universal banks have the bulk of the assets of the financial system, microfinance institutions (MFIs) reach more clients (around 8 million) through over 3,000 outlets spread throughout the country. Although not all such institutions were directly regulated by the Bank of Ghana (BoG), capacity building, oversight and monitoring support from MFI Associations and donor-supported programs helped ensure stable growth. During the late 2000s, however, new types of unregulated microfinance service providers proliferated, increasing the number of operators who lacked sufficient capacity, skills, governance, transparency, and accountability to act as responsible financial intermediaries. This posed a risk to the sector, with increasing incidents of reported fraud, insolvency, and loss of savings by low-income households. In 2011, BoG initiated measures to bring all types of MFIs under a consistent regulatory framework by issuing Guidelines for MFIs. This paper summarizes the situation and development of microfinance institutions in Ghana, reviews progress and problems in implementing the BoG regulations for MFIs, highlights current risks and challenges, and proposes strategies for mitigating risks. The analysis includes three different levels: BoG and Government of Ghana (GoG); MFIs and their associations; and the public. It is aimed at providing information on the complex issues in the microfinance sector as a basis for dialogue on concrete reforms.